Cleaning and preserving bindings and related materials - Horton, Carolyn (Chicago : Library Technology Program, American Library Association, 1969)
The primary purpose is to provide a manual that will be useful to both the skilled and unskilled librarians in the practice of conservation of library materials
Bibliography: p. 73-81.
obn 22/01/2019
Loans
Keywords: Books